К предпосылкам и етапам перехода и.-е. *s в *š в языках группы сатǝм - Едельман, Джой И. (Baltistica, 1994)
ON PRECONDITIONS AND STAGES OF THE TRANSITION OF IE *s TO *š IN THE LANGUAGES OF THE SATǝM GROUP The data of the Aryan languages show that the process of transition of *s to *š-type sounds under certain phonetic (articulatory) conditions, which had begun in IE dialects of the Satǝm group in earlier times on the phonetic level, has resulted on phonological level in appearance of the opposition s š much later, after the Satǝm group had diverged into subgroups and even after the divergence of the Aryan protolanguage. The phonologization of the opposition s š was proceeding in parallel, independent and not identical ways in each “branch“ (Indian, Iranian, and Nuristani — „Kafiri“) of the Aryan languages, and was closely connected with entire phonological systems of these languages. Some „systematic exclusions“ witness that phonological „ruki-rule“ was not a distinctive feature of the separation of the Satǝm group from other IE dialects (as well as the Aryan group from other Satǝm dialects). The change of *s to *š-type sounds in position after *i, *r, *k, and — in various dialects — after some other phonemes (in most of the dialects, after *u and later, in Iranian, after labial consonants, etc.) was only a common Satǝm phonetic tendency that accompanied (to different degrees in different areas) much more significant transformations of IE palatal (and in some dialects, palatalized velar) consonants. This tendency from the early times was often blocked up by processes of lexical, grammatical and phonetical analogy (different in various languages), which obscure the results of the „ruki-rule“.